Visual analytics for inspecting the evolution of a graph over time: Pattern discovery in a communication network - Schneider, Bruno; Acevedo, Carmela; Buchmuller, Juri; Fischer, Fabian; Keim, Daniel A. (2015 IEEE Conference on Visual Analytics Science and Technology (VAST), 2015)
We present two approaches developed to visually analyze and find patterns in a communication network. The work was done for the VAST 2015 Mini-Challenge 2 (MC2), featuring a dataset with records of timestamps as well as identification of sender and receiver of text messages. Further information included the location from which a message was sent in the fictional amusement park. In the first approach, we present the data preprocessing pipeline we used for a custom visualization. In the second approach, we present how we used available data preprocessing and visualization software to get a quick and clear overview of the problem, and how we used the generated findings to feed our custom visualizations.